Use of sequence barcodes for tracking horizontal gene transfer of antimicrobial resistance genes in a microbial community - Partanen, Veera; Dekić Rozman, Svjetlana; Karkman, Antti; Muurinen, Johanna; Hiltunen, Teppo; Virta, Marko (Oxford University Press (OUP), 2026)
One of the most important knowledge gaps in the antimicrobial resistance crisis is the lack of understanding regarding how genes spread from their environmental origins to bacteria pathogenic to humans. In this study our aim was to create a system that allows the conduction of experiments in laboratory settings that mimic the complexity of natural communities with multiple resistance genes and mobile genetic elements circulating at the same time. Here we report a new sequence-based barcode system that allows simultaneous tracking of the spread of antimicrobial resistance genes from multiple genetic origins. We tested this concept with an experiment in which we added an antimicrobial resistance gene to different genetic environments in alive and dead donors and let the gene spread naturally in an artificial microbial community under different environmental conditions to provide examples of factors that can be investigated. We used emulsion, paired-isolation, and concatenation polymerase chain reaction to detect the new gene carriers and metagenomic analysis to see changes in the genetic environment. We observed the genes moving and were able to recognise the barcode from the gene sequences, thus validating the idea of barcode use. We also saw that temperature and gene origin had effects on the number of new host species. Our results confirmed that our system worked and can be further developed for more complicated experiments.